Relationship Between Emotion Regulation and Suicide Ideation and Attempt in Adults and Adolescents: A Systematic Review. - Colmenero-Navarrete, Lidia; García-Sancho, Esperanza; Salguero-Noguera, José Martín (Taylor & Francis, 2021)
Introduction: Suicide is one of the main causes of death in adults and adolescents, so research focused on identifying risk factors for suicidal behavior is needed. In recent years, emotion regulation, mainly the presence of difficulties regulating one´s own negative emotions, has been associated with negative mental health outcomes. Objective: The purpose of this study was to systematically review the available evidence on the association between emotion regulation and suicide (ideation and attempt) in both adults and adolescents. Method: A systematic search of scientific articles published in English and Spanish was carried out through the databases PsycINFO, MEDLINE, Scopus, and the Cochrane Library. Results: We identified 76 eligible studies, of which 70 reported that people with difficulties in emotion regulation reported higher levels of suicide ideation and more suicide attempts. The results were consistent in adolescents and adults, in clinical and general population samples, and when studies assessed both emotion regulation processes and strategies. However, few studies were longitudinal and most of them were with women. Conclusions: We discuss the theoretical implications of the results, suggesting that actual psychological models might benefit from considering individual differences in ER in understanding why people engage in suicide behavior. Clinical implications are also discussed.
https://v2.sherpa.ac.uk/id/publication/4956
Keywords: Suicidio - Factores de riesgo; Suicide; Emotion regulation; Systematic review